Principles Based On The Teaching Of Mathematics Using Application Programs In Higher Education Institutions - Kuljonov N. J. (Euro Asian Journal Publishing, 2024)
Digitization and PPs are effective in the proper organization of students' learning activities in mathematics. Students are given the opportunity to independently solve examples and problems related to the topic and analyze their results. At the same time, it serves to master mathematics and increase interest in science. It also helps to form motivation in relation to the activity.
Keywords: Practical program; digitalization; educational activities